Marginal employment, unemployment duration and job match quality - Marco Caliendo; Steffen Künn; Arne Uhlendorff (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
In some countries including Germany unemployed workers can increase their income during job search by taking up marginal employment up to a threshold without any deduction from their benefits. Marginal employment can be considered as a wage subsidy as it lowers labour costs for firms owing to reduced social security contributions, and increases work incentives due to higher net earnings. Additional earnings during unemployment might lead to higher reservation wages prolonging the duration of unemployment, yet also giving unemployed individuals more time to search for better and more stable jobs. Furthermore, marginal employment might lower human capital deterioration and raise the job arrival rate due to network effects. To evaluate the impact of marginal employment on unemployment duration and subsequent job quality, we consider a sample of fresh entries into unemployment. Our results suggest that marginal employment leads to more stable post-unemployment jobs, has no impact on wages, and increases the job-finding probability if it is related to previous sectoral experience of the unemployed worker. We find evidence for time-varying treatment effects: whilst there is no significant impact during the first twelve months of unemployment, job finding probabilities increase after one year and the impact on job stability is stronger if the jobs are taken up later within the unemployment spell.
Keywords: J64; C41; C33; 330; marginal employment; unemployment duration; job search; employment stability; timing of events model